Curriculum in higher education : Confusion, complexity and currency. - Hicks, Owen (HERDSA Review of Higher Education v.5 p.5-30, 2018)
Curriculum in higher education has received increased attention in recent years, particularly in the context of whole-of-institution curriculum renewal. Most recent academic literature favours a broad definition of curriculum as a process for connecting and integrating university learning and teaching into coherent and meaningful educational experiences for students. However, in an environment seen as increasingly more complex and commercial, the term curriculum continues to be used in differing or undefined ways, often limited to a focus on the content and structure of programs. The concept appears ubiquitous in higher education but there has been limited explicit use of the term. Over the last two decades a notable increase in research into curriculum in higher education has occurred, notably in Australia and the surrounding region. A range of current issues, such as internationalisation, blended learning, curriculum mapping, and research-related learning have reinvigorated interest in curriculum. Greater attention needs to be given to evaluation of curriculum initiatives, while the future currency of the term will depend on a realisation of its utility. [Author abstract]